Technological change and industry competitiveness through the evolution of localised comparative advantages - The case of Italy - Daniela Palma; Alessandro Zini (European Regional Science Association (ERSA), 2005)
The influence of technological change on industry performances is nowadays being increasingly investigated under the broad category of "national systemic competitiveness". Moreover theoretical works have shown that the relationship between technology and economic performance not only takes different forms in different socio-economic contexts, but is also powerfully influenced by the way that innovation processes evolve over time along strongly localised patterns. The present study is focused on the evolution of trade competitiveness of the manufacturing sector in Italy over the past ten years and addresses to the role played by localised comparative advantages in shaping the model of national competitiveness. The data used in the analysis, drawn by the Enea Observatory on high tech industries, are based on trade statistics at the SITC five digit level and are spatially referenced to the Italy NUT3 regional partition. The effects of localised trade specialisation on manufacturing competitiveness are first assessed through spatial econometric tecniques. Spatial variation in the relationships found is further explored in order to give additional hints on the specific contribution of localised comparative advantages. According to major trends which have recently characterised manufacturing trade competitiveness in Italy, the analysis is expected to bring into evidence significant changes in the contribution of industrial localities to national competitiveness.
Keywords: 330